Health promotion: the relevance of fruits and vegetables and their role in cancer - Panato, Emanuelle; Junior, Américo Wagner; Minardi Mitre Cotta, Rosângela; G.Peluzio, Maria do Carmo; Araújo Tinôco, Adelson Luiz; Horst Bruckner, Claudio (O Mundo da Saúde, 2007)
In time, human beings discovered that fruits and vegetables have not only a high nutritional value, but also medicinal effects, and each species has its own properties. The aim of this work was to point out how to promote health by consuming fruits and vegetables and their role in cancer prevention. Among the main action mechanisms of fruits and vegetables in disease prevention and treatment, mainly cancer, antioxidant activity should be mentioned. The habit of consuming fruits and vegetables generally aids human body metabolism, strengthens cells and helps preventing certain cancer types. Cancer is one of the most common diseases today, being classified as the second causes of death by disease in Brazil. Environmental factors can act so as to increase harmful effects. While researches about diet and cancer continue, researchers agree that to maintain health and possibly to reduce cancer risk, a diet should be adopted low in fat, rich in vegetables and fruits (five daily portions), and the consumption of alcohol and tobacco avoided, besides maintaining a healthy corporal weight. Nevertheless, the number of health promotion programs in relation to foods consumption and its relation with cancer, as well as their action in different parts of the human body is reduced. Considering this, we suggest increasing the number of these programs for promoting better healthy alimentary habits, emphasizing the benefits of fruits and vegetables consumption in cancer prevention.